Movement reinforcement factors related to children's motor skills: a review study in sports education - Mariati, Dian Sri; Sumaryanti, Sumaryanti; Nugroho, Sigit; Yassin, Abdulnassir; Budayati, Eka Swasta (Tanjungpura Journal of Coaching Research, 2024)
Background and Study Aim. Children's motor development is one of the important aspects in shaping children's health and quality of life. Good motor skills not only enable children to participate in various physical activities, but also play a role in their social, emotional and cognitive development. Therefore, it is important for sports educators to understand the factors that influence children's motor development. This study aims to present a comprehensive review of the factors that reinforce children's motor development in the context of sport education.Materials and Methods. This study used a literature review design following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The data used in this study were published articles published in national and international journals. The search for publication articles was carried out using several journal database websites such as ScienceDirect and Google Scholar. Through the literature review, these articles identified key factors related to improving children's motor skills. After the exclusion criteria, only 4 articles were categorized.Results. These factors include physical, psychological and environmental aspects that influence children's motor development. In this study, we investigated the relationship between factors such as physical exercise, children's psychological understanding of movement, the role of teachers in providing appropriate guidance, a supportive learning environment, and external factors such as healthy diet and lifestyle. The findings from this review highlight the importance of a holistic approach in supporting children's motor development.Conclusions. Through a better understanding of the factors that influence children's motor movements, sport educators can design more effective and sustainable programs to improve motor skills as well as overall health at important developmental stages in children's lives.